Language, thought, and consciousness : an essay in philosophical psychology - Carruthers, Peter (Cambridge University Press, 1996)
Do we think in natural language? Or is language only for communication? Much recent work in philosophy and cognitive science assumes the latter. In contrast, Peter Carruthers argues that much of human conscious thinking is conducted in the medium of natural language sentences. However, this does not commit him to any sort of Whorfian linguistic relativism, and the view is developed within a framework that is broadly nativist and modularist. His study will be essential reading for all those interested in the nature and significance of natural language, whether they come from philosophy, psychology or linguistics.